2023
DOI: 10.3390/diagnostics13111961
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical Outcomes in Rotator Cuff Re-Tear Patients Who Had Either an Arthroscopic Primary Repair or Arthroscopic Patch Augmentation for Large-to-Massive Rotator Cuff Tears

Abstract: Background and Purpose: Despite the prevalent incidence of re-tear following rotator cuff repair, there is a notable lack of comparative studies investigating the outcomes between patients with re-tear who underwent primary repair versus those who received patch augmentation for large-to-massive tears. We assessed clinical outcomes of these techniques through a retrospective, randomized controlled trial. Methods: 134 patients diagnosed with large-to-massive rotator cuff tears from 2018 to 2021 underwent surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…They are composed of an acellular extracellular matrix (ECM), which is supposed to reduce the load on the repaired tendon so it can be protected during the healing phase and to induce native tissue to integrate by favoring vascularization and local cellular growth. Biomechanical studies [2,3] showed improvement in initial strength of the construct, as well as recent studies [21][22][23] that supported the clinical benefits of patch augmentation in rotator cuff repair, explained by the reduction in retear rate and pain.…”
Section: Discussionmentioning
confidence: 53%
“…They are composed of an acellular extracellular matrix (ECM), which is supposed to reduce the load on the repaired tendon so it can be protected during the healing phase and to induce native tissue to integrate by favoring vascularization and local cellular growth. Biomechanical studies [2,3] showed improvement in initial strength of the construct, as well as recent studies [21][22][23] that supported the clinical benefits of patch augmentation in rotator cuff repair, explained by the reduction in retear rate and pain.…”
Section: Discussionmentioning
confidence: 53%
“…Special care was taken to avoid strand tangling during this process (Figure 3). After positioning the allogeneic dermal patch underneath the patient's native rotator cuff tendon, the supraspinatus and infraspinatus muscles were augmented with strands that passed through the allogeneic dermal patch [13]. All ties were made using the Samsung Medical Center (SMC) knot technique [14].…”
Section: Superior Capsule Reconstructionmentioning
confidence: 99%
“…After positioning the allogeneic dermal patch on top of the native rotator cuff tendon, the suture-bridge technique was used to fix the lateral side of the allogeneic dermal patch. Two or three lateral anchors were inserted depending on the size of the defect (Figure 6) [13]. After positioning the allogeneic dermal patch on top of the native rotator cuff tendon, the suture-bridge technique was used to fix the lateral side of the allogeneic dermal patch.…”
Section: Patch Graft Augmentationmentioning
confidence: 99%
See 2 more Smart Citations